A prospective study of i-gel in elective laparoscopic gynecological procedures - Mahesh S Patil; Sangita S Page; Ganesh R Choudhari (Asian Journal of Medical Sciences, 2023)
Background: Many studies have been done to compare i-gel with other laryngeal mask airway. However, not many studies have been done to study the clinical uses of the supraglottic airway device, namely, i-gel. Aims and Objectives: The present study was undertaken to study of i-gel in elective laparoscopic gynecological procedures in tertiary health-care center. Materials and Methods: The present prospective observational study was conducted on patients admitted in OBGY ward for laparoscopic procedures during the period September 2019–2021. The study was undertaken after obtaining Ethical Committee Clearance. Informed consent was taken from each patient. Seventy patients, scheduled for various elective laparoscopic gynecological procedures under general anesthesia belonging to ASA class I and II, were included in the study. Results: Majority number of study participants belonged to age group of 50–59 years, that is, 52 (74.3%), while only 5 (7.1%) study participants belonged to age group of 30–39 years. I-gel insertion was successful in single attempt in 69 (98.6%) study participants, while two attempts were needed for 1 (1.4%) participant. In our study, there was no statistically significant difference of i-gel with regard to heart rate, systolic, diastolic and mean blood pressure, and arterial saturation, EtCO2. There was no post-operative complication after completion of procedure. Conclusion: The present study revealed that i-gel may be used safely and successfully in elective laparoscopic gynecological surgeries under general anesthesia with positive pressure ventilation. It offers excellent insertion conditions and adequate jaw relaxation for easy i-gel insertion on the first try.